Valorization of hazelnut cake in compound chocolate: The effect of formulation on rheological and physical properties - Bursa, Kubra; Toker, Omer Said; Palabiyik, Ibrahim; Yaman, Mustafa; Kian-Pour, Nasim; Konar, Nevzat; Kilicli, Mahmut (ELSEVIER, 2021)
The aim of this study was to valorize hazelnut (Corylus avellana L) cake (HC), which is a by-product of hazelnut oil industry, in compound chocolate (HCC) as a partial replacer of sugar and milk originated powders (MOP: skimmed milk and whey powder in equal amounts). D-optimal mixture design was used to optimize HCC formulation. The optimum sugar, MOP, and HC amount were selected as 25.0-40.0, 6.0-21.0, and 0.0-15.0 g/100 g, respectively. The Casson model with high R-2 values (0.9882-0.9948) was used to determine yield stress and plastic viscosity values of samples which were varied between 1.47 and 2.35 Pa, and 1.17-1.42 Pa s, respectively. Furthermore, particle sizes and water activity were determined between 25.67 and 78.20 mu m and 0.31-0.38, respectively. Total phenolic content in HCC samples, their digestibility, and bioaccessibility ranged from 1389 to 3367; 2601-3955 mg GAE/kg, and 112-187% respectively. Also, hardness and brittleness were ranged between 7.85 and 11.55 N and 0.52-1.02 mm, respectively. The sensorial characteristics of the samples along with flow behavior and physico-chemical properties indicated that HC may be used as a healthy and low-cost ingredient in HCC formulation to partially substitute sugar and MOP.
Keywords: Hazelnut cake; Compound chocolate; Mixture design; Bioaccessibility; Food Science & Technology